An improved zero-dimensional model for simulation of TRIGA Mark II dynamic response. (March 2019) - Introini, Carolina; Cammi, Antonio; Lorenzi, Stefano; Magrotti, Giovanni
Abstract: The primary aim of this work is to improve the analysis of the dynamic behaviour of the TRIGA Mark II reactor at the University of Pavia through a zero-dimensional approach. Besides the coupling between neutronics (point-reactor kinetics with six delayed neutron precursors group) and thermal-hydraulics (two-region model, with fuel and coolant) implemented in earlier works, the new model considers also the time behaviour of the mass flow rate due to natural circulation, of the neutron poisons and of the primary and secondary pool temperature. The system of coupled first-order differential equations is non-linear, as some state variables, such as the mass flow rate and the coolant temperature, multiply each other. The Simulink™ programming environment for dynamic analysis and control purposes is used to solve the system. A comparison with experimental data collected on-site for different reactor power transients and with measurements of the poison anti-reactivity during reactor shut-down and of the pool temperature allows the validation of the model. The model results and the experimental data reach a remarkable agreement. In addition, a linear stability analysis of the reactor is performed through the root locus and the stability map in terms of the thermal feedback coefficients. This analysis shows how the power level influences the dynamic of the system, and that, for certain values (always negative) of the fuel thermal feedback coefficient, positive values of the one for the moderator still ensures the system stability. Highlights: Thermal hydraulic model with time evolution of poisons, mass flow rate, pool temperature. The presented model is validated using experimental data. Dynamic behaviour of the TRIGA reactor on the entire operative power range. Both short-term and long-term reactor response is considered. Stability analysis of the TRIGA reactor by means of the root locus method and stability maps.